2019
DOI: 10.1017/s104795111900204x
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict potentially dangerous coronary patterns in patients with transposition of the great arteries after an arterial switch operation?

Abstract: Introduction:Coronary artery complications are the main reason for early mortality after an arterial switch operation. Late complications are relatively rare, and there is no consensus regarding the need or indications for routine follow-up coronary artery evaluations or the best first-line assessment modality. The aim of this study was to present the long-term post-operative frequency of coronary abnormalities in asymptomatic patients with transposition of the great arteries discovered by coronary CT angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…All coronary complications are summarized in Table 2 . Seventeen out of 192 (8.9%) patients [ 19 , 27 , 42 ] were suspected to have myocardial ischemia based on symptoms or exercise testing; after additional examinations, 3 out of 17 patients underwent coronary intervention (PCI or CABG).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All coronary complications are summarized in Table 2 . Seventeen out of 192 (8.9%) patients [ 19 , 27 , 42 ] were suspected to have myocardial ischemia based on symptoms or exercise testing; after additional examinations, 3 out of 17 patients underwent coronary intervention (PCI or CABG).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [ 9 , 42 ] examined coronary anatomy in adults using routine cCT. The combined results of both studies demonstrated that 4 out of 80 (5%) patients were suspected of coronary stenosis.…”
Section: Resultsmentioning
confidence: 99%
“…Given the small number of coronary reoperations, it is unclear whether TBA patients are at increased risk or whether this is related to the prevalent non-usual coronary artery pattern in TBA. Although abnormal coronary artery patterns have been reported as risk factor for early coronary artery obstruction [ 8 , 9 , 26 ], it is suggested that the acquired coronary anatomy after ASO may be more important as a risk factor for late coronary artery obstruction [ 27 ]. Correspondingly, half of the patients necessitating coronary reoperation from this study had a usual coronary artery pattern without problems during coronary artery transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, half of the patients necessitating coronary reoperation from this study had a usual coronary artery pattern without problems during coronary artery transfer. Acquired abnormal coronary anatomy may result from the surgically created pattern after reimplantation and changes by growth, arterial distortion or root dilatation [ 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of 50 asymptomatic patients who underwent computed tomography angiography 14 to 25 years after ASO, 30 (60%) patients had coronary abnormalities such as ostial stenosis, acute branching of a vessel, muscular bridge, kinking, etc. 9 In another study of 40 patients, mostly asymptomatic, 11% had late coronary artery stenosis. 10 The effect that an abnormal coronary pattern has on the long-term occurrence of these abnormalities is unknown.…”
mentioning
confidence: 95%